Two-Steps Hantzsch Based Macrocyclization Approach for the Synthesis of Thiazole Containing Cyclopeptides - Nefzi, Adel (2010)
Macrocyclization via an efficient high-yielding solid-phase intramolecular thioalkylation reaction is described. The reaction of S-nucleophiles with newly generated N-terminal 4-chloromethyl thiazoles led to the desired macrocyclization products 5 in high purities and good overall yields.